2017
DOI: 10.1063/1.5000863
|View full text |Cite
|
Sign up to set email alerts
|

Two-dimensional turbulence in three-dimensional flows

Abstract: This paper presents a review of experiments performed in three-dimensional flows that show behaviour associated with two-dimensional turbulence. Experiments reveal the presence of the inverse energy cascade in two different systems, namely, flows in thick fluid layers driven electromagnetically and the Faraday wave driven flows. In thick fluid layers, large-scale coherent structures can shear off the vertical eddies and reinforce the planarity of the flow. Such structures are either self-generated or externall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 71 publications
(130 reference statements)
4
29
0
Order By: Relevance
“…We also remark that rapidly rotating turbulence, and magnetohydrodynamic and quasi-static magnetohydrodynamic turbulence with strong external magnetic field exhibits quasi 2D behaviour [12][13][14][15][16][17][18]. Sharma et al [14] employed the enstrophy flux derived in Sec.…”
Section: Discussionmentioning
confidence: 99%
“…We also remark that rapidly rotating turbulence, and magnetohydrodynamic and quasi-static magnetohydrodynamic turbulence with strong external magnetic field exhibits quasi 2D behaviour [12][13][14][15][16][17][18]. Sharma et al [14] employed the enstrophy flux derived in Sec.…”
Section: Discussionmentioning
confidence: 99%
“…Bursts are more frequent than transitions in the bistable regime and their statistics therefore are more easily accessible. Furthermore, given the large experimental literature (see Xia et al 2011;Xia & Francois 2017) on the transition between 3-D turbulence and condensation in thin layers, it would be exciting and very important to study the observed bistability experimentally. The biggest advantage of an experiment compared to DNS would be that much longer observation times are possible as well as higher Re.…”
Section: Discussionmentioning
confidence: 99%
“…Condensates in thin layers have been observed experimentally: the first study by (Sommeria 1986) was followed by the important contributions of (Paret & Tabeling 1997, 1998 and more recently by (Shats et al 2005(Shats et al , 2007Xia et al 2008Xia et al , 2009Xia et al , 2011Byrne et al 2011). An up-to-date review of relevant experiments is presented in (Xia & Francois 2017). These experiments operate primarily in the long-time limit in which the condensate is fully developed.…”
Section: Introductionmentioning
confidence: 99%